Perbedaan Pengetahuan Sebelum Dan Sesudah Diberikan Media Leaflet Pada Penderita Hipertensi Di Puskesmas Wilayah Kerja Kecamatan Cakung Jakarta Timur - ati, Rohmi (Poltekkes Kemenkes Semarang, 2021)
Background: According the Riskesdas Prevalence of hypertension there is an 8.9 % rise in the 2018. in 2013 achieve 25.8 % of Riskesdas data . Among the causes of hypertension in Indonesia is the lack of knowledge. Base on data the reasearcher want to analyze the difference in knowledge before and after information is given by Leaflet media to hypertensive people in the East Jakarta Cakung District.Objective: To analyze differences in knowledge before and after the media Leaflets were given to patients with hypertension at the Community Health Center in the Cakung District, East Jakarta.Method: This study quantitative with Pre-experimental design with one group pretest-posttest design. This study used a questionnaire measuring instrument and the intervention was carried out within one week after being given the Leaflet media.Result: Knowledge of hypertension is categorized into two Good knowledge before given leaflet there are twenty seven respondents (56.3%) Knowledge is not good twenty-one respondents (43.8%). After being given the media leaflet the good category increased to forty-six respondents (95.8%) and the bad category became two respondents (4.2%).Conclusion: There is significant relationship between knowledge before and after given the Leaflet media to patients with hypertension in the Work Area Health Center Cakung , East Jakarta.